Research Progress on the Preparation and Modification of Magnetic Nanomaterials and Their Application in Mycotoxin Detection and Removal - LÜ Jianxin, GUO Mengyue, ZHANG Huiru, KONG Dandan, LUO Jiaoyang, YANG Meihua (Shipin Kexue)
Mycotoxins are toxic small-molecular-mass compounds produced naturally by toxigenic fungi. Ingestion of mycotoxin-contaminated products has a high potential to cause carcinogenic, teratogenic, and mutagenic effects in the human body. As mycotoxin residues have been detected in both foods and Chinese herbal medicine, the development of effective methods for rapid and highly sensitive detection as well as green detoxification of mycotoxins has become a research priority. Magnetic nanoparticles have high specific surface area, high surface energy and high magnetic response and hence have great potential for application as magnetic adsorbent carriers in mycotoxin detection and detoxification. This paper summarizes the methods used for the preparation and functionalized modification of common magnetic nanomaterials and their applications in mycotoxin detection and detoxification, and discusses future trends in mycotoxin control.